Phenological studies of selected leaf and plant traits of Didymochlaena truncatula (Dryopteridaceae) in a Brazilian submontane tropical rainforest. (9th November 2014) - de Paiva Farias, Rafael; Erickson Nascimento da Costa, Lucas; Abraão Araújo da Silva, Ivo; Carneiro Leão Barros, Iva
<x xml:space="preserve">Abstract</x> The phenology of the herbaceous fern Didymochlaena truncatula in a Brazilian submontane tropical rainforest is described. A total of 23 individuals were observed over 18 months (May 2012 to October 2013). The number of live leaves, leaf production, leaf mortality, leaf growth, and fertility were recorded monthly and correlated with local rainfall and temperature. The D. truncatula plants remained evergreen with a monthly mean of 6.49 ± 0.75 leaves that were produced almost continuously at a rate of 6.13 ± 1.46 leaves plant−1 year−1. This rate was higher than the leaf mortality rate, which was 4.61 ± 1.27 leaves plant−1 year−1. Monthly leaf growth of the population was correlated with rainfall. Leaf expansion was fastest in the first month after emergence (1.31 ± 1.03 cm day−1). Fertility and leaf production intensity were not correlated with climate factors or seasonal variations. However, leaf mortality was negatively correlated with rainfall, causing variations in the number of leaves throughout the year. These results show that the phenological rhythms of D. truncatula were not equally influenced by climate variations. The phenology of D. truncatula corresponds to the phenology of a small number of aseasonal tropical ferns.